Successful Outcome of Low-Dose S-1 Used to Treat Buccal Squamous Cell Carcinoma - Kazuyuki Yusa; Hideyuki Yamanouchi; Ayako Sugano; Mitsuyoshi Iino (Case Reports in Oncological Medicine)
This case report describes an 86-year-old woman with dormant right buccal squamous cell carcinoma who was able to maintain a reasonable quality of life after being treated with oral low-dose S-1 (80 mg/day). The treatment regimen started in April 2014 and consisted of two weeks of S-1 followed by a one-week interval. The patient remains on this regimen while maintaining her quality of life and she has been under follow-up as an outpatient for 36 months. The outcomes for this patient indicated that low-dose S-1 is a valid anticancer therapy that may help maintain quality of life for some patients with incurable or dormant cancers.